2013
DOI: 10.1177/2042533313490927
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the relationship between placebo and homeopathy and the implications for clinical trial design

Abstract: Placebo appears to be a real neurobiological phenomenon that has evolved through the selection pressure to be able to heal ourselves. The complex language and social structures of humans means that we can attribute meaning to therapeutic encounters with culturally sanctioned authority figures and we can use our attachment to such figures to generate hope for recovery. Different mechanisms may be involved in the neurobiological aspect of placebo including anxiety, learning, conditioning as well as individual ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Over time, remedies such as poison ivy (Rhus toxicodendron), snake venom (Lachesis), table salt (Natrium muriaticum), head lice (Pediculus humanus capitis) were also used. 6 In the light of the information obtained from these studies, Hahnemann; concluded that "a substance that causes various effects (including harmful effects) when given to a healthy creature in large amounts creates a curative effect when given to a person with the same symptoms in an extremely small amount", and this situation is defined as the "law of similars" (similia similibus curanteur or like cures like). 7…”
Section: Introductionmentioning
confidence: 99%
“…Over time, remedies such as poison ivy (Rhus toxicodendron), snake venom (Lachesis), table salt (Natrium muriaticum), head lice (Pediculus humanus capitis) were also used. 6 In the light of the information obtained from these studies, Hahnemann; concluded that "a substance that causes various effects (including harmful effects) when given to a healthy creature in large amounts creates a curative effect when given to a person with the same symptoms in an extremely small amount", and this situation is defined as the "law of similars" (similia similibus curanteur or like cures like). 7…”
Section: Introductionmentioning
confidence: 99%